Associations Between Self-Stigma and Health Promotion Behaviors in Overweight/Obese Patients With Type 2 Diabetes: A Cross-Sectional Study - Shilian Niu; Rao Li; Li Yuan; Dan Huang (Journal of Diabetes Research)
Conclusions: This study found that there was a correlation between the level of stigma and health-promoting behaviors in overweight/obese patients with T2DM. Hypoglycemia, inpatient, GLP-1RA treatment, and stress management significantly predicted stigma among overweight/obese patients. These findings have implications for healthcare providers, as they can develop intervention strategies by assessing the levels of stigma and stress management in overweight/obese patients with T2DM, to help reduce stigma and promote healthy behaviors among these patients.